Penerapan Ekonomi Syariah Pada Koperasi Syariah di Pekanbaru - Erwin, Muhammad (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
This study aims to explore and understand the implementation of sharia economics in sharia cooperatives in Pekanbaru. This study uses a qualitative approach with a qualitative descriptive design to explore the experiences, perceptions, and views of the administrators, cooperative members, and related parties regarding the implementation of sharia principles in cooperative operations. Data were collected through in-depth interviews, direct observation, and documentation. In-depth interviews were conducted with cooperative administrators, cooperative members, and related parties such as local governments and sharia financial institutions, using purposive sampling techniques to ensure that informants have relevant and in-depth information. Observations were conducted in several sharia cooperatives to directly observe the implementation of sharia principles in operational activities. Documentation includes the collection of financial reports, articles of association, and cooperative policies. The results of the study indicate that the implementation of sharia economics in sharia cooperatives in Pekanbaru has been running in accordance with sharia principles, namely without usury, gharar, and maysir. Sharia cooperatives in Pekanbaru function as a forum for the community to carry out fair and sustainable economic activities, with profits distributed evenly to all members. Support from the government and related institutions, as well as increasing public awareness of the importance of sharia economics, are the main factors driving the development of sharia cooperatives in Pekanbaru. However, challenges such as the lack of public understanding of the concept of sharia economics and the need for competent human resources still need to be overcome for better development of sharia cooperatives. This study concludes that with the right support and better understanding of sharia principles, sharia cooperatives in Pekanbaru can continue to grow and make significant contributions to realizing a just and sustainable economy.